A study on physical and personnel security implemented in military married quarters - Nor Isman Idris (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2021)
Safety and security is an important aspect for every living. It is on of the 7 basic human needs according to Maslow (air, water, food, shelter, safety, sleep and clothing). The main aim of this study is to examine the influence of physical security, personnel security, security management system-resident satisfaction and security management system-crime prevention on the safety of military married quarters. Security management system consist of three main components which are people (personnel security) which is cover in this study, technology (physical security) also cover in this study and proces such as policies and procedures are not cover in this study. The study involved 350 officers from the tri-services (Army, Navy and Air Force) from 7 Military Married Quarters in Kuala Lumpur which are RKAT Uthant, Desa Wangsa Keramat, Desa Pasifik, Desa Setiawira, Desa Tunku Mariam, Pangsapuri ATM and Kelumpok Nuri. The data was collected through questionnaire survey and analysed by Statistical Package for Social Science (SPSS). The relationship between independent variables which are physical protection, personal protection, security management system-resident satisfaction and security management system-crime prevention and dependent variable which is safety in military married quarters were analysed. This study found physical protection, personal protection, security management system-resident satisfaction and security management system-crime prevention as a factor that influenced the safety in Military Married Quarters. According to the multiple regression analysis every independent variables had a negative relationship with dependent variables. Finally from the study the role of the residents’ association is very important to govern the guarded neighborhood, and they should play a significant role in order to keep their residents safe and secure from any crime.